Understanding mothers' lived experiences of postpartum depression: a qualitative phenomenological study - Cirban Ekrem, Ebru; Kurt, Aylin; Kilci Erciyas, Seyma (Bmc, 2026)
BackgroundPostpartum depression negatively affects maternal wellbeing, infant development, and family relationships. This study aimed to explore the lived experiences of mothers diagnosed with postpartum depression and to identify the psychosocial factors influencing their condition.MethodsThe qualitative study was conducted with 21 postpartum mothers who scored above the Edinburgh Postnatal Depression Scale cut-off point of 12. Data were collected through in-depth, semi-structured individual interviews and analyzed using interpretative phenomenological analysis.ResultsAnalysis revealed four main themes: (1) sociodemographic factors, (2) pregnancy and childbirth experiences, (3) personal approach, and (4) expectations. Participants reported that the presence of other children, increased household responsibilities, and changes in their pre-pregnancy lifestyle contributed to emotional distress. Traumatic birth experiences, risky pregnancies, and postpartum complications were additional triggers. Mothers described feelings of inadequacy, regret, self-neglect, and difficulty coping with motherhood, while expressing a strong need for emotional support from spouses, families, and healthcare professionals.ConclusionIn the postpartum period, maternal depression may result from a complex interplay of factors, including the physiological effects of pregnancy and childbirth, the psychological impact of the surrounding environment, and sociodemographic variables.
Keywords: Edinburgh postnatal depression scale; Postpartum depression; Maternal mental health; Qualitative research; Thematic analysis; Maternal medicine